The effect of hydrogen concentration on the fracture surface of medium Mn steels. (January 2020) - Liu, Qingyang; Yang, Shuquan; Shen, Liancheng; Zhou, Qingjun; Li, Jinxu; Su, Yanjing; Qiao, Lijie; Yan, Yu
Highlights: Austenite content is the most influential factor on the hydrogen diffusion rate. Dissolved H in austenite can diffuse to the interface during the transformation. Hydrogen promotes local deformation of ferrite by promoting dislocation emission. Abstract: To balance good strength and ductility, Medium Mn steels have been considered as the new generation materials used in automotives. However, they show delayed fracture, which is thought to relate to hydrogen. Therefore, in order to understand their mechanical properties with various hydrogen contents, it is very important to assess their safety. In this study, the effect of hydrogen on the mechanical properties of several medium Mn steels (MMSs) with different Mn content and treatments were investigated. For medium Mn steels, the stability of the retained austenite (RA) was examined and the hydrogen permeation test was performed. Austenite, as a barrier to hydrogen diffusion, leads to a tortuous diffusion path, which reduces the diffusion rate of hydrogen in MMSs. Increasing the Mn content increases the volume fraction of RA in the specimen. The stress-strain curves of MMSs were divided into three parts, determined by the stability and content of RA. Slow strain rate tensile tests with hydrogen charging were performed to investigate the behaviour of hydrogen diffusion and the mechanism of hydrogen embrittlement (HE). After the tests, the hydrogen content was measured and the fracture surface was observed and analysed. The phenomenon of HE in steels has been mainly explained based on the mechanisms of hydrogen-enhanced localised plasticity (HELP), hydrogen-enhanced decohesion (HEDE), and hydrogen assisted micro ovoid coalescence (HDMC). Due to the existence of hydrogen, fracture morphology changes from ductile mode to brittle mode. It was also found that under the same strain rate, tensile strength and elongation decrease gradually as hydrogen concentration increases, resulting in final failure.